Wine branding and consumer behaviour : font and quality perception in the wine market - Colli, Lorenzo (2025)
The goal of this study is to explore the role of font’s choice in shaping consumers’ quality perception of wine quality, with a specific focus on the Italian market. This research investigates whether serif fonts, traditionally associated with elegance and refinement, lead to a perception of higher quality than sans-serif fonts, generally linked to modernity and simplicity. From the survey made for this paper, serif font, traditionally linked with elegance and refinement, were consistently associated with higher quality by respondents, especially for less expert customers, suggesting that traditional aesthetics are very important for individuals who rely more on visual cues rather than product knowledge. Conversely, sans-serif fonts did not yield a significant effect on perceived quality, even among northern Italian consumers, countering initial hypotheses about regional preferences. Furthermore, font choice did not significantly influence purchasing decisions based on the occasion for which the wine was purchased, such as casual versus formal use. These findings provide useful indications for wine producers and marketers, suggesting aligning font choices with broader cultural and aesthetic expectations while maintain brand consistency and appealing to the target audience’s preference. Serif fonts can be used strategically to convey tradition and high quality, whereas sans-serif fonts may be better suited for products aimed at younger, experimental consumers or modern market segments.